IMPACT OF AIRPORTS ON THE ENVIRONMENT: OPINIONS OF LOCAL COMMUNITY REPRESENTATIVES - Marzena; Jarosław KOZUBA; Stanisław SIRKO (Scientific Journal of Silesian University of Technology. Series Transport)
Research presented in this article was undertaken to determine how representatives of authorities and residents of communes perceive airports in the context of the impact of these airports on the socio-economic situation in the communes. The goal was achieved using: analysis of documentation of communes, analysis of data on the functioning of airports, and a diagnostic survey using the interview technique and survey technique. The research was carried out on representatives of 5 communes located in Poland. To analyse the collected material and present the results, Statistica v.13.3, R v.4.0.0 and RStudio editor software were used. Results of this research proved that airports play a pivotal role in stimulating the development of the region. They influence the quality of life in the commune by contributing to the creation of jobs, attracting investors, and generating income for the municipal budget through taxes paid.